2020
DOI: 10.21608/asnj.2021.54495.1090
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles Face Nursing Staff Toward Care of Critically Ill Obese Patient in Intensive Care Units

Abstract: Background: Intensive care unit was a stressful environment. Therefore nurses encounter additional obstacles when caring for obese patients in ICU. These obstacles must be identified for proposing a solution and enhancing safe and quality nursing care to critically ill obese patients. The aim of this study was to assess obstacles that face nursing staff toward the care of critically ill obese patients in the intensive care unit. Design: Cross-sectional descriptive research design. Subject: All available critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Patients with obesity (PWO) stay in hospital (2) due to non-communicable diseases (3), and nurses have to handle challenges even when providing the most basic nursing care for these patients (4). Examples of difficult patient care situations include measuring blood pressure, monitoring hemodynamics, positioning, bathing (5), transferring the patient (5,6), intubating or inserting tracheostomy and a laryngeal mask airway (7,8) palpating the carotid pulse during resuscitation, as well as performing CPR (4) and venipuncture (5). Fat tissue, patients' large size (6), and the lack of treatment-care facilities appropriate to their weights (5,9,10) are the most common causes of patient care challenges, which have consequences for both nurses (such as increased workload (11), fatigue (12), and back injury (13)) and patients such as falling from the bed during difficult movements (14), fracture, head trauma, skin damage, and bedsores, which can cause patient safety incidents (15).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with obesity (PWO) stay in hospital (2) due to non-communicable diseases (3), and nurses have to handle challenges even when providing the most basic nursing care for these patients (4). Examples of difficult patient care situations include measuring blood pressure, monitoring hemodynamics, positioning, bathing (5), transferring the patient (5,6), intubating or inserting tracheostomy and a laryngeal mask airway (7,8) palpating the carotid pulse during resuscitation, as well as performing CPR (4) and venipuncture (5). Fat tissue, patients' large size (6), and the lack of treatment-care facilities appropriate to their weights (5,9,10) are the most common causes of patient care challenges, which have consequences for both nurses (such as increased workload (11), fatigue (12), and back injury (13)) and patients such as falling from the bed during difficult movements (14), fracture, head trauma, skin damage, and bedsores, which can cause patient safety incidents (15).…”
Section: Introductionmentioning
confidence: 99%
“…13,16 In a study of critical care for BBPs, over half of the intensive care unit nurses reported difficulty finding appropriately sized patient gowns. 17 Ill-fitting gowns have also been framed as a form of micro-aggressive fat phobia in maternity care. 18 A case study of the palliative care of a BBP reported that the patient's weight negatively impacted privacy, dignity, moving and handling and hospice transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Patients have different and more care needs due to their large sizes (10,11). Nurses may have difficulty in changing a patient's position (12), transferring them (10), and controlling vital signs while taking care of them (12), all of which can lead to poor quality of care. Healthcare providers have reported poor quality care, unmet needs of PWO (11), and weight bias (e.g., the use of unpleasant words and negative judgments) (13).…”
Section: Introductionmentioning
confidence: 99%